2018
DOI: 10.1016/j.comnet.2018.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Detecting heavy flows in the SDN match and action model

Abstract: Efficient algorithms and techniques to detect and identify large flows in a high throughput traffic stream in the SDN matchand-action model are presented. This is in contrast to previous work that either deviated from the match and action model by requiring additional switch level capabilities or did not exploit the SDN data plane. Our construction has two parts; (a) how to sample in an SDN match and action model, (b) how to detect large flows efficiently and in a scalable way, in the SDN model.Our large flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 13 publications
0
28
0
Order By: Relevance
“…DiffFlow [30] also uses packet sampling to perceive the existence of long flows in the network, but does not explore the sampling performance in detail. Other works include MircoTE [31], OpenSample [32], Sample&Pick [33], etc. These solutions focused on data center network load balancing, and did not have a good answer to how to obtain network long flow information.…”
Section: Samplingmentioning
confidence: 99%
“…DiffFlow [30] also uses packet sampling to perceive the existence of long flows in the network, but does not explore the sampling performance in detail. Other works include MircoTE [31], OpenSample [32], Sample&Pick [33], etc. These solutions focused on data center network load balancing, and did not have a good answer to how to obtain network long flow information.…”
Section: Samplingmentioning
confidence: 99%
“…One solution to this problem is to keep track only the large/heavy flows. A large flow is a flow that includes more than a certain percentage of the packets during a given time interval [Afek et al 2018]. Studies have shown that the majority of flows tend to be short (mice flows) on high-speed links.…”
Section: Design Guidelinesmentioning
confidence: 99%
“…One solution to this problem is to keep track of only the large/heavy flows. A large flow is a flow that includes more than a certain percentage of the packets during a given time interval . Studies have shown that the majority of flows tend to be short (mice flows) on high‐speed links.…”
Section: Introductionmentioning
confidence: 99%